Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1159/000295859
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Transmembrane Conductance Regulator Can Export Hyaluronan

Abstract: Objectives: Hyaluronan, a major water binding component of the extracellular matrix, is synthesised within the cytosol and exported across the plasma membrane by the ABC-transporter MRP5 in fibroblasts. Although its synthesis is vital for embryogenesis, MRP5-deficient mice are without phenotype, suggesting that another transporter had substituted for the MRP5 protein. Thus, we searched for a compensatory exporter in fibroblasts from MRP5 deficient mice and found that cystic fibrosis transmembrane conductance r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 101 publications
(59 reference statements)
0
16
0
1
Order By: Relevance
“…While performing unrelated experiments that involved supplementing cultures of P. aeruginosa with hyaluronan (HA), a host glycosaminoglycan present in CF airways and abundant in inflamed tissues (Gill et al, 2010; Schulz et al, 2010), we observed the formation of morphologically complex biofilms composed of interlaced structures (Figure 1A and B). The addition of hyaluronidase (HA’ase) dissolved these structures (Figure S1A and B), indicating that HA was essential for their formation.…”
Section: Resultsmentioning
confidence: 99%
“…While performing unrelated experiments that involved supplementing cultures of P. aeruginosa with hyaluronan (HA), a host glycosaminoglycan present in CF airways and abundant in inflamed tissues (Gill et al, 2010; Schulz et al, 2010), we observed the formation of morphologically complex biofilms composed of interlaced structures (Figure 1A and B). The addition of hyaluronidase (HA’ase) dissolved these structures (Figure S1A and B), indicating that HA was essential for their formation.…”
Section: Resultsmentioning
confidence: 99%
“…Export from epithelial cells through CFTR can be inhibited by GlyH101 which clogs the channel from outside and thus does not interfere with the intracellular metabolism [Muanprasat et al, 2004;Schulz et al, 2010]. We inhibited hyaluronan export by zaprinast from mouse fibroblasts, and by GlyH101 from MRP5-deficient mouse fibroblast and a human breast cancer cells that both express the CFTR channel.…”
Section: Cell Volume Changes By Hyaluronan Export Inhibitionmentioning
confidence: 99%
“…In addition, elevated concentrations of anionic glycosaminoglycans (GAGs) have been found in mucus samples from children with CF [33] (Figure 2). For example, significantly increased bronchial levels of hyaluronic acid have been reported [34], with sputum concentrations 100-fold higher than in acute bronchitis. Moreover, CF sputum has been shown to contain significantly elevated levels of chondroitin [35] and heparan sulphate [36] and in vitro enzymatic digestion of GAGs with chondroitinase ABC rather than protein digestion with trypsin decreased viscoelasticity of CF purulent sputa [37].…”
Section: Physical Properties Of Airway Mucus In Cystic Fibrosismentioning
confidence: 99%